2010
DOI: 10.1038/mi.2010.6
|View full text |Cite
|
Sign up to set email alerts
|

Control of RSV-induced lung injury by alternatively activated macrophages is IL-4Rα-, TLR4-, and IFN-β-dependent

Abstract: Severe RSV-induced bronchiolitis has been associated with a mixed “Th1” and “Th2” cytokine storm. We hypothesized that differentiation of “alternatively activated” macrophages (AA-Mϕ) would mediate resolution of RSV-induced lung injury. RSV induced IL-4 and IL-13 by murine lung and peritoneal macrophages, IL-4Rα/STAT6-dependent AA-Mϕ differentiation, and significantly enhanced inflammation in lungs of IL-4Rα−/− mice. Adoptive transfer of wild type (WT) macrophages to IL-4Rα−/− mice restored RSV-inducible AA-Mϕ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
223
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(231 citation statements)
references
References 45 publications
5
223
0
3
Order By: Relevance
“…In parallel, however, counter-regulatory cytokines, such as IL-4 and IL-13, are also produced during RSV infection [52]. In response to IL-4 and IL-13, monocytes differentiate into "alternatively activated macrophages" that display anti-inflammatory activities and, in mouse models of RSV-induced infection, contribute to resolution of lung disease [53]. Other cytokines with potential "anti-inflammatory" activity, such as IL-6 and IL-10, were detected in clinical studies from nasopharyngeal secretions of infants with RSV-induced LRTIs [54][55][56].…”
Section: Rsv Infection and Host Immune Responsementioning
confidence: 99%
“…In parallel, however, counter-regulatory cytokines, such as IL-4 and IL-13, are also produced during RSV infection [52]. In response to IL-4 and IL-13, monocytes differentiate into "alternatively activated macrophages" that display anti-inflammatory activities and, in mouse models of RSV-induced infection, contribute to resolution of lung disease [53]. Other cytokines with potential "anti-inflammatory" activity, such as IL-6 and IL-10, were detected in clinical studies from nasopharyngeal secretions of infants with RSV-induced LRTIs [54][55][56].…”
Section: Rsv Infection and Host Immune Responsementioning
confidence: 99%
“…Basophils can produce IL-4 in HRSV-infected mice, but these cells are rare (Moore et al, 2009b). The finding that macrophages can express TH 2 cytokines in response to HRSV (Shirey et al, 2010) is potentially very important because T H 2 cytokines (especially mucus-associated IL-13) are thought to contribute to HRSV disease and, as noted above, HRSV, BRSV, and PVM lung pathology in the natural host is characterized by prominent macrophage accumulation in bronchiolar and alveolar spaces.…”
Section: Hrsv Infection Of Cotton Ratsmentioning
confidence: 99%
“…An interesting recent study performed with HRSV Long strain showed that HRSV treatment of mouse peritoneal and alveolar macrophages induces these macrophages to become www.intechopen.com alternatively activated to express TH 2 cytokines IL-4 and IL-13, and infection of cotton rats with HRSV Long increased markers of alternatively activated macrophages (Shirey et al, 2010). Although the role of TH 2 cytokines in HRSV pathogenesis has been controversial, most studies have focused on a T cell source of these cytokines, e.g.…”
Section: Hrsv Infection Of Cotton Ratsmentioning
confidence: 99%
“…It has also been shown that human alveolar macrophages can produce IL-4 (Pouliot, et al, 2005). It has been shown that infectious pathogens including Francisella tularensis and respiratory syncitial virus (RSV) induce lung and peritoneal macrophages to produce IL-4 and IL-13 , Shirey, et al, 2010. Fig.…”
Section: Myeloid Cellsmentioning
confidence: 99%